Reflecting on international academic mobility through feminist lenses: moving beyond the obvious - França, Thais; Padilla, Beatriz (Comparative Cultural Studies: European and Latin American Perspectives, 2017)
Academic mobility has always been a reality in academia, however nowadays it has gained new meanings and features. On the one hand, it brings benefits such as knowledge circulation, international network promotion, and reduction in experimental costs. On the other hand however, it reproduces old social hierarchies and power asymmetries. Gender is on important marker of difference that shape academic mobility experiences unevenly, therefore women face more obstacles than men to develop their academic career. This paper analyses academic mobility through a feminist perspective aiming to reinforce the importance of taking gender differences in account in this dynamics.